ANALISIS YURIDIS PENJATUHAN PIDANA TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN ANAK YANG MENGAKIBATKAN KEMATIAN DI KOTA PONTIANAK (STUDI KASUS PUTUSAN NOMOR 17 Pid.Sus-Anak/2019/PN.Ptk) - NIM. A1011201196, SRI REGAWATI WIRASNATA (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT Currently there are still many children who commit criminal acts, one of which is persecution and some even result in death. It certainly needs law enforcement and the applicable legal basis related to children, especially in the case of child perpetrators who commit acts of child abuse that result in death in Pontianak City with decision number: 17 Pid. Sus-Anak/2019/PN. PTK. In the decision, the child perpetrator committed maltreatment such as hitting, kicking repeatedly against the victim named Ramadhan who was a disabled child. When the victim ran away, the child perpetrator was still waiting for the child to plan another persecution of the victim Ramadhan. When the victim Ramadhan returned, the child perpetrator committed maltreatment again until the victim Ramadhan died. Based on the verdict, the prosecutor charged the juvenile offender with a sentence of 3 (three) years 6 (six) months under Article 76c Jo. Article 80 paragraph 3 of Law No.35 of 2014 on the amendment of Law No.23 of 2002 on child protection. However, the judge decided to impose punishment on the child perpetrator with imprisonment of 2 (two) years 6 (six) months. This means that the judge is not maximal in imposing punishment on child perpetrators who commit child abuse that results in death. Therefore, the formulation of the problem in this study is why judges do not impose maximum imprisonment on child perpetrators who commit child abuse resulting in death in Pontianak City? The method used in this type of research is normative juridical legal research conducted by examining primary and secondary legal materials such as laws, theories, literature studies, and interviews. The results of this study are that the judge in imposing punishment on children should be adjusted to Article 355 paragraph (2) of the Criminal Code on premeditated serious maltreatment which contains